DINAMIKA DALAM PEMEKARAN DESA BUNGARAYA HULU KECAMATAN BUNGARAYA KABUPATEN SIAK 2011 - Supriadi S; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research is motivated by the implementation of the division yet Bungarayavillage Bungaraya Siak Hulu subdistrict, whereas the expansion requirement hasbeen met. This study aims to determine the dynamics of the expansion of thevillage in the district of Hulu Bungaraya Bungaraya Siak in 2011 Until Now. Thelocation of this research is located in the village of the District BungarayaBungaraya Siak. Subjects were those who knew or completeness of theinformation nor the object of research. In this study researchers used informantsthrough key informants. Key informants in this study were sub-district BungarayaSiak and Bungaraya Village Head, Chairman of BPD (Village Consultative Body)Bunga Raya village, village secretary, BPMPD (Agency for CommunityEmpowerment and Village Government). Engineering major or primary datacollection using interviews / interview. Results reveal that the splitting of thevillage of Bunga Raya Hulu has become a dynamic to be resolved. In the villagehead Bunga Raya no problems, while in the sub-district head said divisionproblems should be studied and should be resolved at the district level. Then,when viewed from the requirements and regulations of the Minister of the Interiordivision of the village, that village Bunga Raya Hulu has met all the requirementscorrectly. The latter is an indication of the importance of other parties to hinderthe process of dividing the village of Bunga Raya Hulu.Keywords: Dynamics, village expansion